2021
DOI: 10.4251/wjgo.v13.i2.147
|View full text |Cite
|
Sign up to set email alerts
|

Rare common bile duct metastasis of breast cancer: A case report and literature review

Abstract: BACKGROUND Breast cancer is the most common tumor in women, and about one-third of cases develop metastatic disease. However, metastatic breast cancer rarely invades the common bile duct (CBD) directly without involving the liver, and involvement of the gastrointestinal tract is rare. Cases of such metastases pose a particular diagnostic challenge. CASE SUMMARY A 55-year-old female presented to the Department of Gastroenterology with complaint of a 2 mo history of right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…7 Moreover, Tang et al reported that endoscopic ultrasound for metastatic bile duct tumor revealed a widening of the bile duct wall. 8 Unfortunately, endoscopic ultrasound/intraductal ultrasound was not performed in this case, but endoscopic ultrasound/intraductal ultrasound often produces findings similar to those for gastrointestinal subepithelial tumors, which might provide a modality to facilitate diagnosis. Furthermore, secondary sclerosing cholangitis should be regarded as a possible differential diagnosis for such findings.…”
Section: Discussionmentioning
confidence: 93%
“…7 Moreover, Tang et al reported that endoscopic ultrasound for metastatic bile duct tumor revealed a widening of the bile duct wall. 8 Unfortunately, endoscopic ultrasound/intraductal ultrasound was not performed in this case, but endoscopic ultrasound/intraductal ultrasound often produces findings similar to those for gastrointestinal subepithelial tumors, which might provide a modality to facilitate diagnosis. Furthermore, secondary sclerosing cholangitis should be regarded as a possible differential diagnosis for such findings.…”
Section: Discussionmentioning
confidence: 93%
“…These case reports were obtained through a search of PubMed for articles published from 1946 to 2021, using the search terms "breast cancer" and "biliary metastasis". In addition to these, Japanese case reports were obtained through a search of the Japana Centra Revuo Medicina Web for articles published from 1977 to 2021, using the Japanese equivalents of the search terms mentioned above [2][3][4][5][6][7][8][9][10][11][12][13] . The details of these case reports are presented in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these, Japanese case reports were obtained through a search of the Japana Centra Revuo Medicina Web for articles published from 1977 to 2021, using the Japanese equivalents of the search terms mentioned above. 1,[3][4][5][6][7][8][9][10][11][12][13][14] The details of these case reports are presented in Table 1. The average age of the patients was 56 years (42-70 years).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding treatment for objective jaundice by bile duct stenosis, only five cases were treated by endoscopic drainage (Table 2). 1,3,4,6 To patients who might respond to other modes of therapy enabling longer survival, surgical bypass could be more effective than endoscopic treatment. 12 But in our case, endoscopic drainage was chosen because metastases were found in multiple organs other than the bile ducts, so long-term prognosis was not promising, and also because of the invasiveness of surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation